Preterm birth. Treatment and evidences - Pacheco Romero, José (2015)
We do a brief account on evidence-based preterm birth treatment, emphasizing the importance of appropriate clinical, ultrasound and laboratory diagnosis. Tocolysis may decrease uterine activity and uterine cervix modifications but does not lower preterm birth rates; it may prolong gestation though to allow corticoids administration and in utero fetus transportation to a specialized unit. If we have to use a tocolytic agent, beta agonists are no longer first line drugs, and atosiban and nifedipine have less adverse maternal effects. A single dose of corticoids between 24 and 34 weeks of gestation reduces preterm death, respiratory distress syndrome and intraventricular hemorrhage risks. Preterm birth is a social problem of major importance and more emphasis should be placed on primary prevention and treatment of immaturity.